Epidemics and Mortality in Early Modern Japan - Ann Bowman Jannetta (Princeton University Press, 2014)
limiting population growth in preindustrial societies.1 Modern-day microbiologists agree with Malthus: "From the beginnings of agriculture and urbanization till well into the present century infectious disease was the major overall cause of human mortality and the most important stabilizer of population levels."2 Malthus believed that a population would grow until it reached the limit of its resources. A society that had reached "Malthusian" limits would experience periods of population growth interrupted by sharp increases in mortality. "Positive" checks in the form of epidemics, famine, and war would intervene and reduce the size of the population to former levels. Recurring mortality crises were the mechanisms by which people and the resources that sustain them were brought into equilibrium